PENGARUH PEMBERIAN TEKNIK SITZ BATH TERHADAP PENURUNAN NYERI LUKA PERINEUM PADA IBU NIFAS DI KLINIK PRATAMA TANJUNG DELI TUA KABUPATEN DELI SERDANG - Sari, Husna; Hayati, Erlina; Marbun, Muliani (JURNAL ILMIAH DHDT - KEBIDANAN, 2025)
During the labor process, wounds often occur in the perineum area, either due to natural tears or episiotomy which will cause pain and discomfort to postpartum mothers due to extensive tissue damage. Therefore, prevention and management of pain are very important, one of which is with the sitz bath technique. This study aims to determine the effectiveness of the sitz bath technique in reducing pain in postpartum mothers with perineal wounds of grade 1 and 2 at the Tanjung Deli Tua Pratama Clinic. With a single group pre-test and post-test design, this study employed a quasi-experimental methodology, involving 13 postpartum mothers selected through purposive sampling. The Numerical Rating Scale (NRS) was used to gauge the severity of the pain. Using the Wilcoxon test to analyze data showed a p value = 0.002 (p <0.05), which means that there is a significant effect of the sitz bath technique on lessening discomfort from perineal wounds. The findings of this investigation suggest that health workers not only provide pharmacological therapy to overcome perineal wound pain, but can also combine it with sitz bath techniques as an effective non-pharmacological therapy.